Prevalence, clinical profile, and laboratory features of hospitalized under-five children with rotavirus-induced diarrhea - Jyothirmayi, P; Kamble, D Dnyanesh; Patil, V D (Indian Journal of Child Health, 2018)
Background: Rotavirus is considered as an important causative agent for pediatric diarrhea. Despite recent studies, data available on the prevalence of diarrhea due to rotavirus, among under-five children, are scarce. Objective: The objective of this study is to estimate the prevalence, clinical profile, and laboratory features among hospitalized under-five children with rotavirusinduced diarrhea. Materials and Methods: A total of 145 under-five children with diarrhea were included in the study. The sociodemographic characteristics, clinical profile, and laboratory investigations of all the children were recorded. Stool samples collected were tested for rotavirus antigen using enzyme immunoassay. Results: Of 145 stool samples processed, rotavirus antigen was positive in 33.10% of cases, and male-to-female ratio was 1.1:1. The majority (62.76%) of the children with diarrhea were aged ?12 months. Rotavirus infection was significantly associated with socioeconomic status of the parents (p=0.023), maternal education (p=0.028), fever (p=0.029), vomiting (p=0.001), restlessness (p=0.001), perianal excoriation (p=0.045), bottle feeding (p=0.014), hypernatremia (p<0.001), and presence of reducing substances (p 0.001). Conclusion: Rotavirus-induced diarrhea was diagnosed in one-third of the study children. Maternal education, symptoms of fever, vomiting, presence of reducing substances, and age ?12 months were found to be predisposing factors for rotavirus infection in under-five children. However, periodic review on rotavirus and other co-pathogenic infections are required to validate the current findings.